Advances in the Synthesis and Application of Anti-Fouling Membranes Using Two-Dimensional Nanomaterials - Asif Shahzad; Jae-Min Oh; Mudassar Azam; Jibran Iqbal; Sabir Hussain; Waheed Miran; Kashif Rasool (Membranes, 2021)
This article provides a comprehensive review of the recent progress in the application of advanced two-dimensional nanomaterials (2DNMs) in membranes fabrication and application for water purification. The membranes fouling, its types, and anti-fouling mechanisms of different 2DNMs containing membrane systems are also discussed. The developments in membrane synthesis and modification using 2DNMs, especially graphene and graphene family materials, carbon nanotubes (CNTs), MXenes, and others are critically reviewed. Further, the application potential of next-generation 2DNMs-based membranes in water/wastewater treatment systems is surveyed. Finally, the current problems and future opportunities of applying 2DNMs for anti-fouling membranes are also debated.